Analisis risiko operasional berbasis pendekatan Enterprise Risk Management (ERM) pada perusahaan konveksi Rivania Muslim Store - Taufik, Muhammad Irham; Solehudin, Kurniawan; Nada, Qotrun (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Rivania Muslim Store is a garment company that focuses on producing Muslim clothing, this company faces operational risks that can affect the smooth running of its business. This study aims to analyze operational risks using the Enterprise Risk Management (ERM) approach to identify, assess and manage the risks faced by the company. This data was obtained from interviews with business owners and analysis of supporting documents. The results of the study identified five main risks, namely computer errors, production errors, lack of machine maintenance, machine damage during production, and limited labor. These risks are described based on their severity, high risks such as computer errors, lack of machine maintenance and product defects that impact the company's operations.